2017
DOI: 10.1128/jvi.02234-16
|View full text |Cite|
|
Sign up to set email alerts
|

Endoplasmic Reticulum Protein SCAP Inhibits Dengue Virus NS2B3 Protease by Suppressing Its K27-Linked Polyubiquitylation

Abstract: Dengue viruses (DENVs) are an emerging threat to global public health. The NS2B3 protease complex of DENV has recently been shown to cleave the antiviral protein STING and thereby subvert the innate immune signaling to facilitate virus replication. Whether host cells have a mechanism to counteract this virus-mediated immunosuppression is unclear. We discovered that the K27-linked polyubiquitination of NS3 protein facilitates its recruitment of NS2B, the formation of NS2B3, and consequently the enhanced cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Here, we provide direct evidence that ZIKV also targets the cGAS/STING pathway by cleaving STING, impairing the cells' ability to induce ISGs in response to cGAMP, but not poly(I:C), stimulation. Proteolytic inactivation of STING appears to be a general mechanism shared by several other flaviviruses, including JEV, DENV (38)(39)(40)54), and WNV, but not live-attenuated or virulent YFV. We found that the residues R78 and G79, located within the cytoplasmic loop of STING, are critical determinants for NS2B3-mediated cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide direct evidence that ZIKV also targets the cGAS/STING pathway by cleaving STING, impairing the cells' ability to induce ISGs in response to cGAMP, but not poly(I:C), stimulation. Proteolytic inactivation of STING appears to be a general mechanism shared by several other flaviviruses, including JEV, DENV (38)(39)(40)54), and WNV, but not live-attenuated or virulent YFV. We found that the residues R78 and G79, located within the cytoplasmic loop of STING, are critical determinants for NS2B3-mediated cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, upon DNA virus infection, K27-linked polyubiquitination of cGAS and STING can restrict the replication of viruses (54,55). In contrast, K27-linked polyubiquitination of dengue virus NS3 protein enhances the cleavage of STING by the NS2B3 protease complex, promoting viral replication (71).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liu et al . reported that the full‐length DENV NS3 (including the C‐terminal helicase), but not the NS2B, can be modified by Lys27‐linked polyubiquitination when co‐transfecting Ub and NS3 in HEK 293T cells. The ubiquitinated NS3 facilitates recruitment of NS2B, that is, the formation of the NS2B/NS3 protease, thereby enhancing the cleavage of STING.…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immune mentioning
confidence: 99%
“…The ubiquitinated NS3 facilitates recruitment of NS2B, that is, the formation of the NS2B/NS3 protease, thereby enhancing the cleavage of STING. Furthermore, these authors found that the ER protein SCAP (sterol regulatory element‐binding protein (SREBP) cleavage‐activating protein) can bind NS2B and inhibit polyubiquitination of NS3, thus disrupting the formation of NS2B/NS3 pro and the cleavage of STING .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immune mentioning
confidence: 99%